From Upstream to Downstream: Islam and the State Preventing LGBT - Tsalis, Khodijah Nur; Ali, Mardhatillah; Surahman, Surahman (STIS Ummul Ayman, Meureudu, Pidie Jaya, Aceh, Indonesia, 2023)
The state has a constitution and Islam has a sharia that aims to regulate human life so that it runs well and does not violate the eastern norms and values adopted by Indonesian society. This article aims to examine the extent of the state's efforts through the Constitution and Islam through sharia to prevent someone from becoming LGBT. This research is a literature review with the type of normative research that uses the statute approach and phenomenological approach. Based on the analysis, the state and Islam have tried to prevent LGBT early on. The Constitution and Sharia regulate that the family is formed on a good and solid foundation in the face of LGBT issues. However, due to the lack of firmness of the Constitution, LGBT perpetrators still find loopholes to exist and change their appearance to better match the gender they want. At the end of the stage, to legalize the gender transition and be recognized by the state, they apply for a change of identity on the Indonesia Identity card through the Court. The constitution that regulates this change is also considered not firm, all returned to the judgment and decision of the judge to accept or reject their application.